2020
DOI: 10.24018/ejers.2020.5.9.2066
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Delayed Payment in Construction Project in Nigeria

Abstract: Delay in payment to contactors and other relevant parties have caused serious problem on the successful execution of construction projects in the country. It causes several problems to the contractor and other participants. The aim of this study is to determine the causes of delayed payments in the construction industry. The objective of this study is to identify the causes of delayed payment. In order to obtain valid data for the study, questionnaires were designed and distributed to a randomly selected sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Contractors' failure to submit corrected claims [55] Submission of claims with errors [55,56], Present Study Client's failure to cultivate a good payment attitude among their employees by wrongfully withholding the payment [25,55,56], Present Study…”
Section: Critical Factors For the Causes Of The Delayed Payment Refer...mentioning
confidence: 99%
See 1 more Smart Citation
“…Contractors' failure to submit corrected claims [55] Submission of claims with errors [55,56], Present Study Client's failure to cultivate a good payment attitude among their employees by wrongfully withholding the payment [25,55,56], Present Study…”
Section: Critical Factors For the Causes Of The Delayed Payment Refer...mentioning
confidence: 99%
“…The use of 'pay-when-paid' clauses [25,55] Contracts used are not comprehensive enough in terms of payment aspects [55] Contracts used are too complicated to be understood by both parties [55], Present Study Clients' poor financial management [25,55], Present Study Clients' poor financial condition [55] Bureaucratic procedures [57,13] Slow process of approving variations [56,57,13], Present Study Ripple effects of an economic downturn [57,13] Poor Process Implementation [13,57] Acceptability of Late Payment [13,57] Client's disagreeing on the valuation of project executed [25,56] Delay in certification by the consultants [25, [56] Poor quality of work [56] Design changes during construction Present Study…”
Section: Critical Factors For the Causes Of The Delayed Payment Refer...mentioning
confidence: 99%
“…A study by Checherita et al (2015) on the payment discipline of governments to private sector, found out that payment delays led to a greater likelihood of bankruptcy, liquidity problems and declined profits. Abdul-Rahman (2009) reviewed financial related causes from the project delivery perspective, while Seboru (2015) reviewed the factors causing delays but from project delivery dimension, whereas other studies, embarked on causes and effects of delayed payments ( Odenigbo, 2018;Obodoh and Obodoh, 2016;Okeyo et al ,2015;Kwame, 2011;Assaf and Al-Hejji, 2005;Aibunu and Jagboro 2002;Mezher and Tawil 1998;Mansfield, 1994), with some studies in Kenya zero-in to road contractors (Akali and Sakaja, 2018;Mwangi, 2016;Seboru, 2015) whereas other studies focussed only on financial performance (Bhunia.et. al 2016;Muna, 2015;Halim.et.…”
Section: Payment Delays and Financial Performancementioning
confidence: 99%
“…Tayeh et al, 2020, identified the causes of VO as lack of materials and equipment spare parts due to closure, change in design by a consultant, lack of consultant's knowledge of available materials, errors and omission in design, conflicts between contract documents, owner's financial problems, lack of coordination among project parties, using the inadequate specification for local markets by an international consultant, internal politics, and change is a specification by owners [3]. Odenigbo et al, 2020, suggested the causes of VO as client, consultant, contractors, and others. Ghafoor et al, 2020, stated that the essential steps in developing a variation order are the scope definition.…”
Section: Introductionmentioning
confidence: 99%
“…Ghafoor et al, 2020, stated that the essential steps in developing a variation order are the scope definition. A poorly defined scope will not provide a clear baseline, leading to the variation order that will be evaluated within or outside the scope [4], [5]. Hassana et al, 2018, suggested that consultants should understand the overall scope and goals of the project.…”
Section: Introductionmentioning
confidence: 99%